Nanoparticle Internalization Promotes the Survival of Primary Macrophages. Issue 5 (9th February 2022) - Jarai, Bader M.; Fromen, Catherine A.
Abstract : Macrophages, a class of tissue resident innate immune cells, are responsible for sequestering foreign objects through the process of phagocytosis, making them a promising target for immune modulation via particulate engineering. Herein, it is reported that nanoparticle (NP) dosing and cellular internalization via phagocytosis significantly enhance survival of ex vivo cultures of primary bone marrow‐derived, alveolar, and peritoneal macrophages over particle‐free controls. The enhanced survival is attributed to suppression of caspase‐dependent apoptosis and is linked to phagocytosis and lysosomal signaling. Uniquely, poly(ethylene glycol)‐based NP treatment extends cell viability in the absence of macrophage polarization and enhances expression of prosurvival B cell lymphoma‐2 (Bcl‐2) protein in macrophages following multiple routes of in vivo administration. The enhanced survival phenomenon is also applicable to NPs of alternative chemistries, indicating the potential universality of this phenomenon with relevant drug delivery particles. These findings provide a framework for extending the lifespan of primary macrophages ex vivo for drug screening, vaccine studies, and cell therapies and have implications for in vivo particulate immune‐engineering applications. Abstract : Nanoparticle (NP) treatment to macrophages causes enhanced ex vivo survival following a single dose. NP phagocytosis triggers lysosomal signaling, which promotes prosurvival factors and suppresses proapoptotic pathways. NP‐induced survival occurs in the absence of aberrant inflammatory effects. This phenomenon is applicable to a wide range of NP types and chemistries and is observed in different populations of primary macrophages.